The information master: Jean-Baptiste Colberts secret state intelligence system (cultures of knowledge in the early modern world). - Soll, Jacob (Cultures of knowledge in the early modern world, 2010)
Jean-Baptiste Colbert saw governance of the state not as the inherent ability of the king, but as a form of mechanical mastery of subjects such as medieval legal history, physics, navigation, and the price lists of nails, sails, and gunpowder. In The Information Master , Jacob Soll shows how the legacy of Colbert’s encyclopedic tradition lies at the very center of the rise of the modern state. This innovative book argues that Colbert's practice of collecting knowledge originated in Renaissance Italy, where merchants recognized the power to be gained from merging scholarship and trade. By connecting historical literatures—archives, libraries, merchant techniques, and humanist pedagogy—that have usually remained separate, Soll has created an imaginative and refreshing work.